A series of Cre‐ERT2 drivers for manipulation of the skeletal muscle lineage. Issue 8 (3rd June 2014) - Southard, Sheryl; Low, SiewHui; Li, Lydia; Rozo, Michelle; Harvey, Tyler; Fan, Chen‐Ming; Lepper, Christoph
Summary We report the generation of five mouse strains with the tamoxifen‐inducible Cre (Cre‐ERT2; CE) gene cassette knocked into the endogenous loci of Pax3, Myod1, Myog, Myf6, and Myl1, collectively as a resource for the skeletal muscle research community. We characterized these CE strains using the Cre reporter mice, R26RLacZ, during embryogenesis and show that they direct tightly controlled tamoxifen‐inducible reporter expression within the expected cell lineage determined by each myogenic gene. We also examined a few selected adult skeletal muscle groups for tamoxifen‐inducible reporter expression. None of these new CE alleles direct reporter expression in the cardiac muscle. All these alleles follow the same knock‐in strategy by replacing the first exon of each gene with the CE cassette, rendering them null alleles of the endogenous gene. Advantages and disadvantages of this design are discussed. Although we describe potential immediate use of these strains, their utility likely extends beyond foreseeable questions in skeletal muscle biology. genesis 52:759–770, 2014. © 2014 Wiley Periodicals, Inc.